Bioactivities Screening of Indonesian Marine Bacteria Isolated from Sponges - Artanti, Nina; Maryani, Faiza; Mulyani, Hanny; Dewi, Rizna Triana; Saraswati, Vienna; Murniasih, Tutik (BRIN, 2016)
Currently marine bacteria are considered as important source of natural products for drug discovery. The objective of this study is to conduct an in vitro bioactivities (antidiabetic, antioxidant and antibacterial) screening of 9 Indonesian marine bacteria isolated from sponges that belongs to the Research Center for Oceanography, Indonesian Institute of Sciences collections. The marine bacteria were cultured for 2 days in liquid medium containing yeast, peptone and sea salt under shaking condition and extracted with ethyl acetate. Antidiabetic was measured using inhibition of -glucosidase inhibitory activity method; antioxidant was measured using DPPH free radical scavenging activity method; antibacterial was tested using disc diffusion method. Screening results showed that at sample concentration of 200 μg/mL, there was significant -glucosidase inhibitory activity detected in the extracts of strain Sp 7.9 (84 % inhibition) and Sp 8.10 (75 % inhibition), however the antioxidant activities of these two strains were low only around 30 % inhibition, antioxidant activities of other strains were very low. Screening for antibacterial activities using 10 μL samples show that extract of strain Sp 8.5 was best for Staphylococcus aureus (14 mm inhibition); Sp 7.9, and Sp 8.5 for Bacillus subtilis (18 mm inhibition); Sp 8.10 for Escherichia coli (10 mm inhibition); Sp 8.9 and Sp 8.10 (10 mm inhibition) for Pseudomonas aeuriginosa. Based on these results marine bacteria strain Sp 7.9 and Sp 8.10 were selected to be used for further studies in the isolation of bioactive that has potential as antidiabetic and antibacterial. Results of molecular identification conducted by InaCC show that identity of both strains based on BLAST Homology using NCBI database were Bacillus thuringiensis.